Pharmaceutical Standardization Of “ ” Prepared By Electric Muffle Furnace - Arjaria, Anamika; Upadhyay, Shankar Dayal; Pati, R K (International Research Journal of Ayurveda & Yoga, 2020)
Kupipakwa Rasayana, a superlative form of preparation in Rasa Shastra. Rasa Sindoora (Red sulfide of mercury) is one of the best formulations of Kupipakwa Rasayana in Ayurveda. Rasa Sindoora has proven its efficacy in a wide spectrum of ailments over the time with different herbal drugs and Anupaan in variety of doses. Equal ratio of Shodhita Parada (Purified Mercury) and Shodhita Gandhaka (Purified Sulphur) were used to prepare Rasa Sindoora as per the reference of Rasa Tarangini with wide expansion of therapeutic effect. Aim- To standardize manufacturing procedure of Rasa Sindoora. Material and method- Rasa Sindoora preparation was standardized by preparing three batches using electric muffle furnace (EMF). Results- In three consecutive batches of Rasa Sindoora, The average yield was 104.66 gm in average time of 12.53 hrs. In all three batches average of Kajjali melting temperature, flame appearing temperature and corking temperature were 3540C, 4840C and 6010C respectively. Conclusion- Rasa Sindoora preparation was concluded on the basis of three batches in which each batch of 200 gm of Kajjalisubjected to following intermittent heating pattern that was mild heat (100-2500C) for 4 hrs, Moderate heat (250-4500C) for 4 hrs and strong heat (450-6500C) for 4 hrs. The average yield was 104.66 gm i.e. 52.33%.